DNA repair capacity and response to treatment of colon cancer - Vodicka, Pavel; Vodenkova, Sona; Buchler, Tomas; Vodickova, Ludmila (Pharmacogenomics, 2019)
DNA repair, a complex biological process, ensures genomic integrity. Alterations in DNA repair, occurring in many cancers, contribute to the accumulation of mutations in the genome, resulting in genomic instability and cancer progression. DNA repair also plays a substantial role in response to chemotherapeutics: rapidly dividing colon cancer cells, vulnerable to DNA-damaging agents and overcoming DNA repair, undergo cell death. DNA repair capacity represents a complex biomarker, integrating gene variants, gene expressions, the stability of gene products, the effect of inhibitors/stimulators, lifestyle and environmental factors. Here, we discuss DNA repair capacity in sporadic colon cancer, a frequent malignancy worldwide, in relation to tumor heterogeneity, prognosis and prediction, measurements in surrogate and target tissues and suggest important tasks to be addressed.
Keywords: regulace genové exprese u nádorů; epigeneze genetická; Prognosis; buněčná smrt; Humans; Mutation; Colonic Neoplasms; nestabilita genomu; prognóza; Cell Death; poškození DNA; DNA Damage; Epigenesis, Genetic; Gene Expression Regulation, Neoplastic; nádory tračníku; lidé; DNA Repair; oprava DNA; mutace; Genomic Instability